Catheter-related Bloodstream Infections: A Root Cause Analysis in a Series of Simultaneous Ochrobactrum anthropi Infections - Caroleo, Benedetto; Malandrino, Pasquale; Liberto, Aldo; Condorelli, Dario; Patanè, Federico; Maiese, Aniello; Casella, Filomena; Geraci, Diego; Ricci, Pietrantonio; Di Mizio, Giulio (Current Pharmaceutical Biotechnology, 2019)
Objective: Catheter-related bloodstream infections (CRBSIs) pathogenesis is complex and multifactorial mostly due to cutaneous microorganisms migration through the catheter insertion site and catheter tip colonization. Ochrobactrum anthropi is a gram-negative bacterium belonging to the Brucellaceae and related infections are especially observed in immunocompromised patients. Methods: Therefore, O. anthropi infection prevention and surveillance are relevant issues for healthcare system and risk management, in order to improve healthcare quality and patient safety. Four cases of anthropi-related CRBSIs occurring in immunodepressed patients under chemotherapy treatment are reported and the possible prevention and surveillance strategies are analyzed. Results: In the reported cases, all infections occurred almost simultaneously in the Oncology Unit, leading to hypothesize an identical infection source. Subsequently, a clinical audit was performed in order to investigate infection origin and implement prevention and control strategies. Clinical audit allowed to identify the hand hygiene defects as the primary source of the infections, responsible for catheter flushing solution contamination. Conclusion: The aim of this study is to reveal how through correct root cause analysis and clinical audit, several measures could be undertaken in order to promote the prevention of the CRBSIs risk.
Keywords: Ochrobactrum anthropi